Validitas dan Keterbacaan LKPD Berbasis Model Pembelajaran Randai untuk Peserta Didik Kelas XI SMA - Fauziyah Arda; Fitri Arsih; Helendra Helendra; Yosi Laila Rahmi (FONDATIA, 2022)
The low critical thinking skills of students in the human skeletal system material, due to Biology learning has not implemented learning models and teaching materials that facilitate students to practice critical thinking skills. This type of research is development research using 4-D models (four-D models), which is limited to the development stage. The research subjects were two Biology lecturers, FMIPA UNP, two Biology teachers, and 31 students of Class XI Science at SMAN 2 Lintau Buo. This study uses data analysis techniques, namely descriptive statistics. The results showed that the LKPD based on the RANDAI model from the validity test was very valid with a value of 94.25%. While the readability test by the teacher was very well read with a value of 92.26% and read very well by students with a value of 92.69%. LKPD based on the RANDAI learning model has been produced on the Human Movement System for Class XI SMA/MA which is very valid and reads very well.